Nutritional status of crops in agroforestry production systems with African Palm (Elaeis guineensis Jacq.) - Furcal-Beriguete, Parménides (2023)
The objective was to evaluate the nutritional status of the crops of an agroforestry system (SAF), of the monoculture Elaeis guineensis and the absorption of nutrients from Cordia megalantha at the age of two years. Five three-year-old plots established by the Initiative Osa & Golfito (INOGO) were sampled in different locations in the southern region of Costa Rica. Each plot consisted of two treatments: a SAF composed of E. guineensis, C. megalantha, T. cacao and Musa sp, and the monoculture of E. guineensis. On two occasions (2019 and 2020), in each plot leaves and fruits were sampled on five plants randomly selected in the crops, to determine nutrient content; in C. megalantha only three trees were measured, obtaining, in addition, the annual growth; however, to obtain the unit yield of wood, used in nutrient absorption, about 50% of the trees planted were measured (42 trees/ha). The results were statistically analyzed with the plots as blocks, where the variable nutritional status of E. guineensis in the two treatments showed no significant differences, in this crop the recurrent deficient nutrients in the leaves were Zn and K. Meanwhile, T. cacao and Musa sp. had greater deficiencies in the content of Ca-Mg-Zn and K-Zn respectively. It was estimated that, on average, one hectare of C. megalantha aged two years extracted in kg: 3.04 ca; 3.04 of N; 1.95 K; 0.48 kg of Mg and 0.23 kg of P.